New word cognitive of Chinese fantasy novel among non-native learners / Bok Check Meng and Goh Ying Soon - Check Meng, Bok; Ying Soon, Goh (Research Management Institute (RMI), Universiti Teknologi MARA, 2016)
Since the 1990s last century, Chinese fantasy novels have become more and more popular among the website readers. Some of the novels were clicked million times. The problem is lack of Mandarin vocabulary for today's nonnative learners so they unable to enjoy themselves into the story and information hiding in the Chinese fantasy novels. For example, students of Faculty Office Management in Universiti Teknologi MARA only learn 600 Mandarin vocabulary within two semester. These amount of Mandarin vocabulary are not enough especially in the informatic era of the rise of China. One day later non-native learners may face a problem to communicate with Chinese people because a lot of Chinese new words must confuse them.